Cosmogenic nuclide evidence for minimal erosion across two subglacial sliding boundaries of the late glacial Fennoscandian ice sheet - Harbor, J.; Stroeven, A. P.; Fabel, D.; Clarhall, A.; Kleman, J.; Li, Y. K.; Elmore, D.; Fink, D. (Purdue University, 2006)
The existence of sliding and frozen bed areas under ice sheets is significant in understanding basal thermal regimes, patterns of erosion and landform development, and in constraining boundary conditions for the reconstructions of ice sheets. Recognition of subglacial boundaries between sliding and frozen-bed areas for former ice sheets is typically based on distinct morphological contrasts between areas with glacial landform assemblages and relict areas showing little alteration of pre-existing features. Some of these boundaries, especially on continental shield areas, however, are clearly visible from air photos but have minimal topographic expression. Understanding the chronology and erosional development of such boundaries is important to provide insight into the pattern and persistence of basal conditions under ice sheets. Geomorphic evidence and cosmogenic radionuclide concentrations of bedrock outcrops on either side of two sliding boundaries on Ultevis and Arvestuottar, low-relief upland plateaus in northern Sweden, are consistent with negligible erosion in relict landscape (frozen bed) areas due to the last glaciation, but also indicate insignificant erosion in the sliding areas. Such a pattern and magnitude of landscape modification indicates that sliding was short lived in these areas, likely as a transient phase during deglaciation. These sites demonstrate that short periods of sliding are in some cases sufficient to produce landscapes that are recognized as 'glacial' from air photos. Thus, regions of sliding identified on shield areas must be viewed as the cumulative total area that has experienced sliding at any time during a glaciation. The actual extent of sliding areas during any single ice sheet phase is presumably considerably less than this cumulative total, which has important implications for establishing appropriate basal boundary conditions for ice sheet reconstructions. (c) 2005 Elsevier B.V. All rights reserved.